2021
DOI: 10.3389/fonc.2021.642142
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Fine-Needle Aspiration Versus Fine-Needle Capillary Sampling in Evaluation of Lymph Node Metastasis of Thyroid Cancer

Abstract: BackgroundTo compare the sampling adequacy and diagnostic efficiency of ultrasound-guided fine-needle aspiration with 22-, 25-gauge needles and capillary sampling with 22-gauge needle in the biopsy of cervical lymph node.MethodsA total of 130 cervical lymph nodes from 103 patients were consecutively included in the prospective study. Each suspected lymph node was aspirated with a 22-gauge needle, capillary sampled with a 22-gauge needle and aspirated with a 25-gauge needle. The adequacy rates and nondiagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…In terms of diagnostic yield of FNA, some studies reported no difference when comparing head and neck specimens obtained with a 21-gauge needle and a 25-gauge needle [ 17 ], or between 23-gauge needle and a 27-gauge needle [ 18 ]. Another study looking at thyroid FNA showed that biopsies using 25-gauge needles have a higher yield than those using 22-gauge needles [ 19 ]. Ultrasound guidance was utilized in both of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnostic yield of FNA, some studies reported no difference when comparing head and neck specimens obtained with a 21-gauge needle and a 25-gauge needle [ 17 ], or between 23-gauge needle and a 27-gauge needle [ 18 ]. Another study looking at thyroid FNA showed that biopsies using 25-gauge needles have a higher yield than those using 22-gauge needles [ 19 ]. Ultrasound guidance was utilized in both of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, mesmo que a PAAF seja considerada o método padrão ouro para a caracterização dos nódulos de tireoide, a técnica é subjetiva, apresentando de 5 a 10% de resultados falsos negativos (San Laureano et al, 2020) e 15 a 30% de resultados indeterminados, fazendo com que na maioria das vezes seja necessária a realização da ressecção do nódulo (Oczko-Wojciechowska et al, 2020;Seneldir et al, 2020;Hejaz et al 2022). Tendo em vista as dificuldades no diagnóstico preciso destes tumores, uma melhor compreensão dos mecanismos moleculares que contribuem para a carcinogênese da tireoide poderá auxiliar na conduta clínica dos pacientes com nódudos citologicamente indeterminados pela PAAF e assim permitir um diagnóstico mais acurado e eficaz (Rodrigues et al, 2019;Xia et al 2021;Chen et al 2022), evitando cirurgias desnecessárias de ressecção, além de auxiliar em novas opções de prognóstico e tratamento dos pacientes (Joo et al 2022).…”
Section: Introductionunclassified